Alteration Alteration, Mineralization and Geochemistry of Metamorphic Rocks Hosted Hydrothermal Gold Deposit at Rumbia Mountains, Bombana Regency, Southeast Sulawesi, Indonesia - Hasria Hasria; Arifudin Idrus; I Wayan Warmada (UIR PRESS, 2019)
In Indonesia, gold is commonly mined from porphyry, epithermal and skarn type deposits that are commonly found in volcanic/magmatic belts. However, were recently numerous gold prospects discovered in association with metamorphic rocks. This paper is intended to describe an alteration and ore mineralogy hosted by metamorphic rocks at Rumbia mountains, Bombana regency, Southeast Sulawesi province, Indonesia. The study area is found the placer and primary gold hosted by metamorphic rocks. The placer gold is evidently derived from gold-bearing quartz veins hosted by Pompangeo Metamorphic Complex (PMC). This study is conducted in three stages, three stages including desk study, field work and laboratory analysis. Desk study mainly covers literature reviews. Field work includes mapping of surface geology, alteration and ore mineralization as well as sampling of representative rocks types, altered rocks and gold-bearing veins. Laboratory analysis includes the petrologic observation of handspecimen samples, petrographic analysis of the thin section and ore microscopy for polished section, XRD (X-ray diffraction), ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy), ICP-MS (Inductively Coupled Plasma Emission Mass Spectrometry and FA/AAS (Fire Assay/Atomic Absorbtion Spectophotometry) analysis. The results shows that the alteration characteristics of hydrothermal gold deposits in Mendoke and Rumbia mountain consist of 3 (three) alterations namely sericitic, argillic dan propylitic. Characteristics of mineralization hydrothermal gold deposits in the research area are generally p related to gold-bearing quartz veins/veinlets consist of chalcopyrite, pyrite, chrysocolla, covellite, cinnabar, magnetite, hematite and goetite in rocks categorized into greenschist facies. There are three generations of veins identified including the first is parallel to the foliations, the second crosscut the first generation of veins/foliations, and the third is of laminated deformed quartz+calcite veins at the late stage. The quartz veins commonly deformed, segmented, massive, laminated, irregular, brecciated, and occasionally sigmoidal. The veins contain erratic gold in various grades from below detection limit <0.0002 ppm to 18,4000 at found in third generation veins which are laminated quartz±calcite in argillic alteration. ppm. The protoliths of metamorphic rocks in Rumbia Mountain, which comes from sedimentary rocks, spesifically pelitic rocks and graywacke. Based on those characteristics, it obviously indicates that the primary gold deposit present in the study area is of orogenic gold deposits type. The orogenic gold deposit is one of the new targets for exploration in Indonesia.